Correlación entre la inversión pública y la pobreza en el departamento de Loreto periodo 2016 - 2020 - Rodríguez Angulo, Erika (2023)
Economic theory postulates that when public investment increases, poverty tends to decrease, and there is an inverse relationship between them. The objective of this research is to determine the correlation between public investment and poverty in the department of Loreto in the period 2016 - 2020. Based on this objective, this Quantitative, Correlational level and design master thesis is executed. Not Experimental. The investigation concludes that there is no relationship between public investment and poverty, endorsed through the statistical test that results in the Correlation Coefficient being r = 0.286706455; and the Coefficient of Determination R2 = 0.082200591; which shows the lack of statistical association and determination between the aforementioned variables. The level of government that concentrates the greatest investment during the study period is Local Governments, with an amount of S/. 1,636.80 million, which is equivalent to 37.50% of the total public investment. The economic function called Transportation and Communications was the main destination of public investment in Loreto, registering the sum of S/. 1,428.40 million, meaning 32.72% of the total value. In second place, Education appears with the value of S/. 854.80 million, equivalent to 19.58% of the total. Poverty in Loreto had a variable behavior during the five years, having been reduced until 2019, but grew to 40.60% in 2020.